Deconvoluting the Complexity of Reactive Oxygen Species (ROS) in Neurodegenerative Diseases - Zhou, Yuxin; Zhen, Yongqi; Wang, Guan; Liu, Bo (Frontiers in Neuroanatomy, 2022)
Neurodegenerative diseases (NDs) have been becoming a serious public health concern as the world's population continues to ageing, demanding for the discovery of more effective therapies. Excessive formation of reactive oxygen species (ROS) can result in oxidative stress (OS), which can be regarded as one of the common causes of neurodegenerative diseases (NDs). Thus, in this review, we focus on summarizing the consequences of ROS NDs, while taking the four prevalent NDs as examples, including Alzheimer's disease (AD), Parkinson's disease (PD), Amyotrophic lateral sclerosis (ALS), and Huntington's disease (HD), to illustrate the key signaling pathways and relevant drugs. Together, these findings may shed new light on a field in which ROS-related pathways play a key role; thereby setting the groundwork for the future therapeutic development of neurodegenerative diseases.